Characterization of the expression pattern of the Caf1 regulator of gene expression in the malaria parasite Plasmodium falciparum - Manivannen, Veronica Lavanya (2016)
Project title: Characterization of the expression pattern of the Caf1 regulator of gene expression in the malaria parasite Plasmodium falciparum.